POHACI - Hartanto, H., (Institut Seni Indoensia Surakarta, 2015)
This research on art work is entitled â€œPohaciâ€, (Hartanto, S. Sn., M. Sn., 2012, 50 pages). The GrantsÂ are funded by DIPA 2012 ISI Surakarta. Pohaci is a dance which is inspired by the story of Dewi SriÂ or Nyai Pohaci Sanghyang Sri, the rice goddess story from West Java. This work takes the figure ofÂ Dewi Sri as a reflection of Javanese women who have the elegance, beauty, softness, flexibility,Â goodness and perfection of a woman. The creation lasts for 27 minutes which is performed as a newÂ form of work. The problem of research includes how the story of Sanghyang Sri Pohaci treated in aÂ different concept is and how the form of the dance work â€œPohaciâ€ is. The purpose of the study is asan abstraction of the female figure as well as the contents which will be realized in art form throughÂ Bedhayan genre. In addition, it adds knowledge and repertoire of dance work that comes from theÂ literature of arts. The method used in the research is interpretation and construction. Interpretationmethod is a method through interpretation of the various elements on the content, form, movement,Â music, fashion and make up lighting. Construction method is a method to do the activity of composingÂ starting from the movement design until the work composition.Alpha The result of study is the dancework â€œPohaciâ€ which pick up the figure of Dewi Sri which is identified by Javanese women. The formÂ of treatment is Bedhayan using seven (7) female dancers accompanied by Javanese gamelan and itsÂ development.Keywords: Pohaci, the art of dance, Dewi Sri, Javanese women.